A fresh look at the fossil evidence for early Archaean cellular life. - Brasier, M; McLoughlin, N; Green, O; Wacey, D (2006)
The rock record provides us with unique evidence for testing models as to when and where cellular life first appeared on Earth. Its study, however, requires caution. The biogenicity of stromatolites and 'microfossils' older than 3.0 Gyr should not be accepted without critical analysis of morphospace and context, using multiple modern techniques, plus rejection of alternative non-biological (null) hypotheses. The previous view that the co-occurrence of biology-like morphology and carbonaceous chemistry in ancient, microfossil-like objects is a presumptive indicator of biogenicity is not enough. As with the famous Martian microfossils, we need to ask not 'what do these structures remind us of?', but 'what are these structures?' Earth's oldest putative 'microfossil' assemblages within 3.4-3.5 Gyr carbonaceous cherts, such as the Apex Chert, are likewise self-organizing structures that do not pass tests for biogenicity. There is a preservational paradox in the fossil record prior to ca 2.7 Gyr: suitable rocks (e.g. isotopically light carbonaceous cherts) are widely present, but signals of life are enigmatic and hard to decipher. One new approach includes detailed mapping of well-preserved sandstone grains in the ca 3.4 Gyr Strelley Pool Chert. These can contain endolithic microtubes showing syngenicity, grain selectivity and several levels of geochemical processing. Preliminary studies invite comparison with a class of ambient inclusion trails of putative microbial origin and with the activities of modern anaerobic proteobacteria and volcanic glass euendoliths.